2021
DOI: 10.1002/clc.23735
|View full text |Cite
|
Sign up to set email alerts
|

Cardio‐ankle vascular index as a predictor of major adverse cardiovascular events in metabolic syndrome patients

Abstract: Background: Arterial stiffness, as reflected in the cardio-ankle vascular index (CAVI), is a risk factor for major adverse cardiovascular events (MACEs).Hypothesis: Combining CAVI and metabolic syndrome (MetS) may enhance prediction of MACEs in a general adult population.Methods: A total of 3807 employees of the Electricity Generating Authority of Thailand were enrolled in a longitudinal health study during 2007-2008. Baseline characteristics were collected and CAVI determined. Subjects with previous coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In a large European multicentre study, a significant impact of MS on PWV was confirmed, although heterogeneous effects of MS components on AS parameters [ 89 ]. In a prospective study involving 3807 subjects, it was documented that patients with MS and AS assessed by the cardio–ankle vascular index (CAVI) have the worst prognosis, with the highest percentages of major adverse cardiovascular events such as myocardial infarction, stroke, or cardiovascular death compared to patients without MS or MS with normal range of CAVI index [ 90 ]. AS, defined by CAVI, has been reported to be a predictor of cardiovascular events, independent of conventional risk factors for atherosclerosis [ 91 ].…”
Section: Metabolic Syndrome and Pulse Wave Velocitymentioning
confidence: 99%
“…In a large European multicentre study, a significant impact of MS on PWV was confirmed, although heterogeneous effects of MS components on AS parameters [ 89 ]. In a prospective study involving 3807 subjects, it was documented that patients with MS and AS assessed by the cardio–ankle vascular index (CAVI) have the worst prognosis, with the highest percentages of major adverse cardiovascular events such as myocardial infarction, stroke, or cardiovascular death compared to patients without MS or MS with normal range of CAVI index [ 90 ]. AS, defined by CAVI, has been reported to be a predictor of cardiovascular events, independent of conventional risk factors for atherosclerosis [ 91 ].…”
Section: Metabolic Syndrome and Pulse Wave Velocitymentioning
confidence: 99%
“…Second, the study population included only Asian individuals. Although several studies on non-Asian populations have been reported [12,14], the generalizability of our data to other races/ethnicities remains uncertain. Third, we failed to estimate the cutoff value of CAVI for each event because of the small number of events.…”
Section: Discussionmentioning
confidence: 78%
“…Several studies have shown that CAVI is associated with the incidence of cardiovascular events in patients with known CVD [5][6][7][8][9] and without CVD [10][11][12][13][14][15][16]. However, evidence on the incremental value of CAVI over a clinical risk score for predicting cardiovascular events has been limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular disease is the leading cause of death worldwide. Several risk factors have been identified and, among these, increased arterial stiffness has gained attention due to its correlation with many cardiovascular endpoints [ 1 ]. Studies reported the determinants of arterial stiffness [ 2 ], which contributes to the stiffening of the wall artery.…”
Section: Introductionmentioning
confidence: 99%